Middle third clavicle fracture osteosynthesis. Functional mid-term results - Del Gordo D’Amato, Roberto Joaquin; Acuña Pinilla, Jose; Torres Carrillo, Efren Camilo (Revista Colombiana de Ortopedia y Traumatología, 2015)
Introduction: Clavicle fractures have been treated historically by different types of immobilization. Recently, the therapeutic approach has gradually shifted to the surgical management. The aim of the study is to determine the results of a cohort of patients who underwent surgery for treatment of clavicular fractures. Materials and methods: A prospective longitudinal cohort, including 66 patients who underwent surgery for middle third clavicle fractures from April 2009 until September 2010, who underwent to open reduction and internal fixation with locked anatomical plate (LCP) osteosynthesis was performed. The 66 patients were followed using visual analogue scale (VAS) and functional Constant score at six weeks, three months, six months and one year after surgery. Results: Statistically significant changes were introduced in progressive improvement in pain and function in each monitoring period (p < 0.001), with no change in pain score between the sixth month follow up evaluation and year follow-up evaluation (p = 0.083). Similarly, high levels of satisfaction was evaluated in both, EVA and Constant scale thorough follow up time. Discussion: It was concluded that open reduction and internal fixation of fractures of the middle third of the clavicle represent an excellent alternative of treatment for such injuries, with a promptly and fully functional recovery and low probability of complications. Evidence level: III.